Analisis Brand Equity Pocari Sweat Dalam Persaingan Industri Minuman (Studi Kasus: Mahasiswa di Bogor) - Pratama, Fredie; Munandar, Jono M. (IPB University, 2010)
Isotonic drink is a new kind of product in Indonesian consumer goods. This kind of product entered Indonesian market in mid-80s. However, isotonic drink industry is growing up along with the increase of people’s welfare and awareness of body health. One of isotonic drinks marketed in Indonesia is Pocari Sweat, produced by PT Amerta Indah Otsuka, which is the market leader in Indonesian isotonic drink industry. High level of competition put more burdens on the producer. PT Amerta has to ensure that Pocari Sweat get a strong position on consumers’ minds. The objective of this research is to analyze Pocari Sweat’s brand equity. It covers several elements: brand awareness, brand association, brand’s perceived quality and brand loyalty. In order to see the overall competition among isotonic drinks, this research also involves several other brands such as ProSweat, Mizone, Aqua, and Coca-Cola. This research is conducted in three universities in Bogor; Bogor Institute of Agriculture (Institut Pertanian Bogor), Pakuan University and Ibnu Khaldun University. The result shows that in the element of brand awareness, Pocari Sweat is the most memorized brand. The association of brand image in brand association element shows that Pocari Sweat has two brand images: safe for health and fresh taste to kill thirst. Analysis on perceived quality with biplot method shows that Pocari Sweat has several attributive characteristics namely benefit, safe for health, eliminates dehydration and recharge stamina. Meanwhile, analysis in brand loyalty shows that Pocari Sweat doesn’t have a strong brand loyalty yet.